Correlation study on gut microbiota and myosteatosis in patients with liver cirrhosis - Ninghui Zhao; Jinjia Bai; Xinmiao Li; Guofen Xu; Xiujuan Fu; Jing Li; Lingyun Niu; Jia Yao; Xiaoshuang Zhou (Frontiers in Nutrition)
ObjectiveTo investigate the features of gut microbiota in cirrhotic patients with myosteatosis and identify specific bacterial species that may be involved in the pathogenesis of myosteatosis.Methods80 patients with liver cirrhosis were categorized into the myosteatosis group (n = 44) and the non-myosteatosis group (n = 36). Metagenomic sequencing was used to analyze the differences in gut microbiota composition between the two groups. Subsequently, the value of meaningful gut microbiota in the diagnosis of myosteatosis in patients with liver cirrhosis was analyzed.ResultsAt the species level, however, 15 bacterial species exhibited significant differences in relative abundance between these two groups. The relative abundance of Roseburia hominis and Subdoligranulum unclassified was inversely associated with mean muscle attenuation density at the L3 level (p < 0.05). Assessement of the diagnostic potential of Roseburia hominis and Subdoligranulum unclassified for the development of myosteatosis showed that the areas under the ROC curves (AUCs) was 0.869 [95% confidence interval (CI): 0.709–1.029; p < 0.05] for Roseburia hominis and 0.828 (95% CI: 0.6472–1.009; p < 0.05) for Subdoligranulum unclassified.ConclusionOur study establishes compositional alterations of gut microbiota in patients with liver cirrhosis combined with myosteatosis and suggests the diagnostic potential for using gut microbiota as noninvasive biomarkers.